Twee dieregestaltes by N.P. van Wyk Louw: Raka en ‘Die swart luiperd’ - Van Heerden, Neil; Visagie, Andries (Tydskrif vir letterkunde, 2018)
As one of the most influential Afrikaans poets of the Dertiger movement, N.P. van Wyk Louw’s work was influenced significantly by modernism and the ideas associated with modernity. His highly canonised poems about animals and human-animal hybrids, Raka (1941), and Die swart luiperd (“The black leopard”) published in 1942 in Gestaltes en diere (Figurations and Animals), present compelling perspectives on the position of nonhuman animals in Afrikaans modernist poetry. In Raka Louw follows the resolute but futile attempts of the culturally refined leader Koki to protect his people against the contaminating effects of the insidious ape-man, Raka. Koki becomes the bearer of Louw’s modernist ideals for the maintenance of higher values. Yet, in his representation of Raka, he preserves something of a counter-image to Koki. As a hybrid creature Raka retains the potential to disrupt teleologies and to insert radical otherness in considerations of cultural excellence. Unlike Koki, the speaker in “Die swart luiperd” plunges into the destabilising depths opened by the gaze of the animal. The encounter with the black leopard in the jungle produces a form of insanity comparable to the experience of Kurtz in Joseph Conrad’s Heart of Darkness. In “Die swart luiperd” Louw dares to break down the boundaries patrolled by Koki in Raka in an apparent rapprochement to the animal as a source of creative revitalisation and extensionof consciousness.